2016
DOI: 10.1007/s11126-016-9473-8
|View full text |Cite
|
Sign up to set email alerts
|

Training Psychiatry Residents in Professionalism in the Digital World

Abstract: Professionalism is an abstract concept which makes it difficult to define, assess and teach. An additional layer of complexity is added when discussing professionalism in the context of digital technology, the internet and social media - the digital world. Current physicians-in-training (residents and fellows) are digital natives having been raised in a digital, media saturated world. Consequently, their use of digital technology and social media has been unconstrained - a reflection of it being integral to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Yet no single, universal definition of physician professionalism exists, instead, healthcare experts and educators have described professionalism using a number of behaviors and characteristics that include fidelity to patient trust, accountability, respect, compassion, integrity, sound ethics, altruism and truthfulness 6 , 7 . Previous studies identified concrete examples of physician behaviors that patients regard as professional, such as formally greeting patients with a handshake and taking notes while speaking to the patient 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Yet no single, universal definition of physician professionalism exists, instead, healthcare experts and educators have described professionalism using a number of behaviors and characteristics that include fidelity to patient trust, accountability, respect, compassion, integrity, sound ethics, altruism and truthfulness 6 , 7 . Previous studies identified concrete examples of physician behaviors that patients regard as professional, such as formally greeting patients with a handshake and taking notes while speaking to the patient 8 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Keefe vs Adams, the eighth US Circuit Court of Appeals ruled that a nursing student could be expelled for Facebook posts that showed a lack of professionalism [ 56 ]. To prevent risks to students and institutions, educators should provide comprehensive and practical guidelines using effective and creative methods (eg, vignettes or simulations) [ 57 , 58 ]. Academic institutions should provide clear policies for students’ social media activities and a safe forum in which all members of the community can constructively discuss controversial issues.…”
Section: Discussionmentioning
confidence: 99%